2012
DOI: 10.1210/en.2012-1290
|View full text |Cite
|
Sign up to set email alerts
|

Isoorientin Reverts TNF-α-Induced Insulin Resistance in Adipocytes Activating the Insulin Signaling Pathway

Abstract: Isoorientin (ISO) is a plant C-glycosylflavonoid with purported antidiabetic effects but unexplored mechanisms of action. To gain insight into its antidiabetic mechanisms, we assayed nontoxic ISO concentrations on the 2-(N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl) amino)-2-deoxy-D-glucose (2-NBDG) uptake by murine 3T3-F442A and human sc adipocytes. In insulin-sensitive adipocytes, ISO stimulated the 2-NBDG uptake by 210% (murine) and 67% (human), compared with insulin treatment. Notably, ISO also induced 2-NBDG upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…Muller et al (2012) demonstrated that the efficacy of aspalathin on glucose uptake was enhanced if used in combination with rutin. Alonso-Castro et al (2011) showed that iso-orientin, also present in GRE in high quantities, increased phosphorylation of both AKT and AMPK culminating in increased glucose uptake in TNF-␣-induced insulin resistant adipocytes which is similar to our findings in C2C12. The role of quercetin, the aglycone of rutin, also present in GRE is controversial.…”
Section: Discussionsupporting
confidence: 90%
“…Muller et al (2012) demonstrated that the efficacy of aspalathin on glucose uptake was enhanced if used in combination with rutin. Alonso-Castro et al (2011) showed that iso-orientin, also present in GRE in high quantities, increased phosphorylation of both AKT and AMPK culminating in increased glucose uptake in TNF-␣-induced insulin resistant adipocytes which is similar to our findings in C2C12. The role of quercetin, the aglycone of rutin, also present in GRE is controversial.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown that increased levels of proinflammatory cytokines, including MCP-1, are involved in obesity and insulin resistance [4, 33] and that excess intake and endogenous release (lipolysis) of saturated fatty acids might enhance expression of TLR-4 target genes including MCP-1. Indeed, TLR-4-deficient knockout mice fed with a diet rich in saturated fatty acid had lower macrophage infiltration and MCP-1 expression in their visceral adipose tissue as compared to wild-type mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are considered a safe approach in treating metabolic syndrome [1], and their therapeutic potential against obesity has been extensively reviewed [2][3][4]. Of interest is isoorientin, a C-glycosyl flavonoid, which is found in rooibos, among other plants, and which displays strong ameliorative effects on obesity-linked complications [5,6]. Isoorientin, also referred to as homoorientin, is a C-glucosyl flavone that was first isolated by Koeppen and colleagues in 1962 from Aspalathus linearis, a South African indigenous plant, which is widely consumed as herbal tea (rooibos) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such limitations have raised interest in expanding research into the use of natural products as therapeutic agents to prevent obesity or its associated complications. Although some studies conducted over the years showed isoorientin, or plants rich in this natural compound, can ameliorate obesity-related complications, such as oxidative stress, inflammation, hyperlipidemia, and insulin resistance [5,[16][17][18][19][20], there is still relatively little information about its impact as a pure compound on obesity.…”
Section: Introductionmentioning
confidence: 99%